STRENGTHS AND WEAKNESSES OF TEACHER’S STRATEGY IN TEACHING PRONUNCIATION - Ali Machfud Rizki (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2021)
Sentence Pronunciation is one of the basic skills in learning English. One of the ways to learn pronunciation can be obtained from teacher’s strategy in teaching. The strategy used by the teacher certainly have the strengths and weaknesses. The research objectives were the strengths and weaknesses of teacher’s strategy in teaching pronunciation. This research used qualitative research to identify what are the strengths and weaknesses of teacher’s strategy using SWOT analysis in teaching pronunciation. To get the data, the researcher used interview. The result shows that the teacher has two categories and three subcategories of the strengths and weakness of teacher’s strategy. The first category is the strengths of teacher’s strategy, this category has got the following subcategories: (a) The strategies made the students pronounce word correctly, (b) The strategies made students’s score good. The second category is the weakness of teacher’s strategy, this category has got the following subcategories: (a) The strategy made the students difficult in understanding material.